New records and species of deep-sea squat lobsters (Galatheoidea, Munidopsidae) from the Hawaiian Archipelago: an integrative approach using micro-CT and barcodes - Paula C. Rodríguez Flores; Kareen E. Schnabel (PeerJ, 2023)
The Hawaiian Archipelago remains extensively under-sampled for many marine invertebrate taxa, including squat lobsters. During the last few years, several deep-sea expeditions carried out in the Pacific Ocean have conducted opportunistic collections of specimens and image data from the vicinity of Hawai’i. Here we describe a new species: Munidopsis hawaii sp. nov. and provide new records for Munidopsidae in the Archipelago and its associations. We illustrate and describe the new species using an integrative approach including micro-CT 3D imaging. Phylogenetic analyses of the species collected from seamounts from Hawai’i indicate that the new species represents a divergent lineage compared to morphologically similar species such as M. dispar and M. papanui. We also study the genetic distances for the species recorded in Hawai’i and other populations of the same species in the adjacent West Pacific. Three species are now known in the Hawaiian region. We also compiled identifications from images captured with ROVs in the area. These observations suggest that munidopsid species are common in the deep sea of Hawaiian waters below 1,000 m.